Design of a Community-Based Waste Management System in Rengas Pulau, Medan Marelan District, Medan City - Hendro David Patar Sibagariang; Fatimah Fatimah; Zulkifli B Lubis (Tunas Geografi, 2023)
The national target for reducing waste in the community is 30% by 2025. This research aims to describe the design of a community-based waste management system and formulate an overview of household waste management policies and strategies in the Rengas Pulau Subdistrict. Based on identifying the affecting factors in waste management, a situation analysis is carried out using a SWOT analysis to formulate 19 (nineteen) strategies to optimize community-based waste management. The design of community-based waste management in Rengas Pulau Subdistrict starts from sorting and processing at the household, collecting and processing at TPS 3R. It is estimated that from the 46.20 m3/day, the volume of waste generation that is targeted to be reduced in the community can be processed and managed by the community in households at 19.52 m3/day (70.41%), and the residue is 8.20 m3/day.Â Meanwhile, household waste processed and managed by KSM at TPS 3R is 13.01 m3 per day (70.40%), and residue is 5.47 m3 per day. Furthermore, the residual waste is transported to TPS and TPA. Communities play a role, from the source of destruction to processing it on a regional scale. The government plays a role by holding a comprehensive waste management outreach and education program and improving the performance of solid waste services. The private sector plays a role by providing support through physical assistance or as an off taker of waste processing products from the community.Keywords: Waste Management, Household Waste, Policy, Community, Government, Private